Kajian QSAR Berbasis Machine Learning dalam Desain Antimalaria Senyawa Turunan Quinolon-4(1H)-imine - Jafar La Kilo (Jambura Journal of Chemistry, 2023)
Study on antimalarial activity of 22 quinolon-4(1H)-imine derivatives by using Quantitative Structure-Activity Relationships (QSAR) has been performed. Electronic and molecular descriptors were used in Quantitative Structure-Activity Relationships (QSAR) model and it was obtained from Hartree-Fock (HF) molecular orbital calculation with 6-31G basis set. QSAR analysis has been performed by multiple linear regression (MLR) method. The best equation of QSAR model on this study is: pEC50 = -4,177 + (37,902 x qC3) + (171,282 x qC8) + (9,061 x qC10) + (125,818 x qC11) + (-149,125 x qC17) + (191,623 x qC18), with statistical parameters, n = 22; r2 = 0,732; SEE = 0,248; Fcal/Ftab = 2,443 and PRESS = 0,925. The best equation can applied to design and predict new compounds with higher antimalarial activity.